Metric handbook : planning and design data - Littlefield, David (London ; New York : Routledge, 2012)
"An essential reference resource for any architect or architect student, the Metric Handbook is the major handbook for planning and design data. For each building type, the book gives basic design requirements, principal dimensional data and details of relevant building regulations. The book also contains information on broader aspects of design applicable to all building types, such as materials, acoustics and lighting, and data on human dimensions and space requirements. Significantly updated, the new edition of this work focuses on sustainable design practice to make projects competitive within a green market. As well as a full revision, including additional new building types and the latest updates to regulation and practice, the book features an improved new layout with color images and text to make it easier to find vital information quickly. Metric Handbook is a tried and tested, authoritative reference for solving everyday planning problems - it is a must have for every design office desk and drawing board"--
Machine generated contents note: (PROVISIONAL) Notation; Basic Design Data; Design and Construction Practice and Techniques; Re-use/Refurbishment/Whole Life Costs ; Design Basics: Buildings & Movement; Design Basics: Spaces/Urban Design; Houses and Flats; Student housing; Homes for the elderly; Hotels; Offices; Retail Trading; Factories and Workshops; Industrial Storage; Agricultural Buildings; Eating and Drinking; Sports Facilities: Indoor; Sports Facilities: Outdoor; Leisure and Community Facilities; Schools and Nurseries; Higher Education; Laboratories; Primary Health Care; Hospitals; Payment offices; Public Buildings; Museums and Art Galleries/Visitor Centres; Libraries and Information Centres / Archives; Terminals and Transport Interchanges; Parking; Sound and Vision Studios; Auditoria; Places of Worship; Structure; Materials; Doors/Windows/Stairs; Heating and Ventilation; Light; Sound; Fire; Security; Designing for the Disabled; Access for Maintenance; Service Distribution.
First ed. published in 1979 as: New metric handbook.
Includes bibliographical references and index.
Keywords: Building -- Details -- Drawings; Metric system